Function-Driven Design of Lactic Acid Bacteria Co-cultures to Produce New Fermented Food Associating Milk and Lupin - Canon, Fanny; Mariadassou, Mahendra; Maillard, Marie-Bernadette; Falentin, Hélène; Parayre, Sandrine; Madec, Marie-Noëlle; Valence, Florence; Henry, Gwénaële; Laroute, Valérie; Daveran-Mingot, Marie-Line; Cocaign-Bousquet, Muriel; Thierry, Anne; et al. (Frontiers in Microbiology, 2020)
Designing bacterial co-cultures adapted to ferment mixes of vegetal and animal resources for food diversification and sustainability is becoming a challenge. Among bacteria used in food fermentation, lactic acid bacteria (LAB) are good candidates, as they are used as starter or adjunct in numerous fermented foods, where they allow preservation, enhanced digestibility, and improved flavor. We developed here a strategy to design LAB co-cultures able to ferment a new food made of bovine milk and lupin flour, consisting in: i) in silico preselection of LAB species for targeted carbohydrate degradation; ii) in vitro screening of 97 strains of the selected species for their ability to ferment carbohydrates and hydrolyze proteins from milk and lupin and clustering strains that displayed similar phenotypes; and iii) assembling strains randomly sampled from clusters that showed complementary phenotypes. The designed co-cultures successfully expressed the targeted traits i.e. hydrolyzed proteins and degraded raffinose family oligosaccharides of lupin and lactose of milk. Moreover, they also reduced an off-flavor-generating volatile, hexanal, and produced various desirable flavor compounds. Most of the strains in co-cultures achieved higher cell counts than in monoculture, suggesting positive interactions. This work opens new avenues for the development of innovative fermented food products based on functionally complementary strains in the world-wide context of diet diversification.